2013
DOI: 10.1155/2013/943409
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Inflammation Associated with Intravitreal Anti-VEGF Pharmacotherapy

Abstract: Vascular endothelial growth factor (VEGF) is a potent promoter of angiogenesis involved in a wide variety of physiologic processes. Intravitreal injections targeting VEGF have transformed the treatment of neovascular retinal diseases. Currently, there are four anti-VEGF agents in use: bevacizumab, ranibizumab, pegaptanib, and aflibercept. The success and frequency of anti-VEGF therapy have made the ocular safety profile of these agents of vital importance. This paper focuses on sterile endophthalmitis. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 51 publications
1
52
1
2
Order By: Relevance
“…The results of the study demonstrated that there was no significant change in aqueous flare values in either IVR- or IVA-injected patients and no significant difference from the control group. There have been previous reports of sterile intraocular inflammation after anti-VEGF injections in the literature [14]. These rates for severe inflammation are low and a large population would be needed for evaluating any difference between anti-VEGF agents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the study demonstrated that there was no significant change in aqueous flare values in either IVR- or IVA-injected patients and no significant difference from the control group. There have been previous reports of sterile intraocular inflammation after anti-VEGF injections in the literature [14]. These rates for severe inflammation are low and a large population would be needed for evaluating any difference between anti-VEGF agents.…”
Section: Discussionmentioning
confidence: 99%
“…Ranibizumab is a 48-kDa recombinant humanized monoclonal antibody fragment, while aflibercept is a 115-kDa recombinant fusion protein [13,14]. As an antibody-binding fragment, ranibizumab lacks the domain that activates compliment-mediated cytotoxicity and Fc receptors on immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several hypotheses concerning the etiology, relating either to the molecule itself or to compounding. [17][18][19][20] First, according to the manufacturer's guidelines (http:// www.gene.com/download/xml/avastin.xml#s2.2), bevacizumab must be stored in the original sterile glass vials at 2°-8° C (36°-46° F) and protected from light. Diluted bevacizumab solution may be stored at 2°-8°C for up to 8 hours.…”
Section: Table 1 Demographic and Clinical Data Of The Patients Affecmentioning
confidence: 99%